2013
DOI: 10.4319/lo.2013.58.4.1185
|View full text |Cite
|
Sign up to set email alerts
|

How pollen organic matter enters freshwater food webs

Abstract: Huge amounts of pollen can accumulate at the air-water interface during the floral bloom of wind-pollinated trees. We hypothesized that such pollen rains act as subsidy pulses, promoting the development of a neustonic microbial food web and the transfer of pollen organic carbon to aquatic consumers. During a pine pollen rain event on an oxbow lake, microorganism concentrations were by far higher in the neuston, where pollen grains accumulated, than in the seston. Zooplankton species were also unevenly distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 46 publications
3
43
1
Order By: Relevance
“…They work best when the fatty acids of interest from different resources have distinct isotopic signatures (Bec et al ). For example, Masclaux et al () revealed that several freshwater zooplankton taxa relied largely on inputs of terrestrial pollen grains that were relatively enriched in δ 13 C as their principal source of ω‐3 HUFAs, while relying on freshwater phytoplankton that was relatively depleted in δ 13 C for their other fats. Thus far most compound‐specific stable isotope work has focused on characterizing food web links in soil communities and in freshwater and marine systems (Ruess and Chamberlain , Gladyshev et al ).…”
Section: Potential For Fatty Acid Limitationmentioning
confidence: 99%
“…They work best when the fatty acids of interest from different resources have distinct isotopic signatures (Bec et al ). For example, Masclaux et al () revealed that several freshwater zooplankton taxa relied largely on inputs of terrestrial pollen grains that were relatively enriched in δ 13 C as their principal source of ω‐3 HUFAs, while relying on freshwater phytoplankton that was relatively depleted in δ 13 C for their other fats. Thus far most compound‐specific stable isotope work has focused on characterizing food web links in soil communities and in freshwater and marine systems (Ruess and Chamberlain , Gladyshev et al ).…”
Section: Potential For Fatty Acid Limitationmentioning
confidence: 99%
“…This mechanism might enhance overall trophic transfer efficiency in the pelagic food web. Chytrids have been shown to upgrade allochthonous organic matter by increasing digestibility of pollen grains and facilitating the transfer of otherwise inaccessible PUFA from pollen to metazoans through chytrid zoospores (Masclaux et al, 2013;Kagami et al, 2017). However, it is unclear if a similar biochemical upgrading of autochthonous carbon sources, such as phytoplankton, occurs upon infection by chytrid parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was suggested that, in detrital food webs, litter-decomposing fungi are colimited by the scarcity of N, P, and S in litter, which they mitigate by foraging on pollen and which allows them to complete litter decomposition (Stark, 1972;Staaf and Berg, 1982;Hutchison and Barron, 1997). Forests may produce pollen in masses reaching 100 to 1000 kg/ha (Greenfield, 1996), and the bulk of this mass is deposited onto forest floors and in lakes (Richerson et al, 1970;Proctor et al, 1996;Shumilovskikh et al, 2015), thus increasing the productivity of the ecosystem (Graham et al, 2006;Masclaux et al, 2013). The present study considers the ecological stoichiometry framework to relate data on pollen nutritional quality to the role of pollen in nutrient cycling within and between terrestrial and aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%